El espacio vitivinícola aragonés como paisaje cultural y factor de desarrollo - Frutos Mejías, Luisa María; Castelló Puig, Ana; Hernández Navarro, María Luz; Loscertales Palomar, Blanca; Ruiz Budría, Enrique; Rubio Terrado, Pascual (Geographicalia, 2014)
At present, the cultural landscape, made up of tangible and intangible elements expressing as it does a prolonged human action on the natural environment, is viewed not only as heritage but as the identity of a society and territory. It is also seen as a resource that enables economic activities to take place and has an impact both on society and on this territory.The wine landscapes meet those requirements. In the following pages, from data that provide sources of information taken from the Ministry of Agriculture, Food and Environment, the Department of Agriculture of the Government of Aragon, the Aragonese Institute of Statistics and the tip regulators of the designation of origin wine, the Aragonese spaces of vineyard with designation of origin will be analyzed, which make up the largest percentage of this crop in Aragon with special emphasis on to the patrimonial character that the long history of its landscapes and their role in rural development has contributed.
Keywords: Wine-growing landscape; cultural heritage; denomination of Origin; Aragon.